Institutional Vulnerability, Breakdown of Trust: A Model of Social Unrest in Chile - Velasco, Andrés; Funk, Robert (Estudios de Economía, 2025)
This paper revisits the standard explanations of the violent Chilean protestsof late 2019, and in particular their exclusive focus on the role of inequality,which in fact had been falling prior to the emergence of unrest. Instead, wesuggest that blame may lie in a crisis of trust in institutions, political and otherwise.We employ a formal model of how trust in government institutions canarise —and also disappear— overnight. In that model, the level of trust is tied(but not uniquely tied) to the level of civic capital in a society. If civic capitalis above a certain threshold, then trust can only be high and increasing, but ifcivic capital is below that threshold, then the outcome is indeterminate, meaningthe level of trust is vulnerable to self-fulfilling bouts of optimism or pessimism.The threshold for civic capital can be shifted by exogenous shocks to parametervalues, including the quality of institutions, with the consequence thatsmall shocks can have small and lasting effects if they take the system from oneregion to another. We document how these dynamics resemble the facts fromChile, where a small drop in reported institutional quality was associated witha large drop in measured trust around the time of the protests. In turn, the protestsinvolved patterns of behavior (like the destruction of urban infrastructure,the evasion of user fees in buses and trains, and the non-repayment of studentloans) which further deteriorated the capacity of the state to provide certainquality public services, and aggravated the decline in institutional trust.